Correlation between Charity and Disaster: A Review of the Traditional of “Sedekah Tolak Bala” in the Langkan Village People Science and Hadith Perspectives - Hasanah, Uswatun (International Journal of Psychosocial Rehabilitation, 2020)
In the village of Langkan there is a tradition of "Sedekah Tolak Bala". This tradition is very trusted and obeyed by the community as a method to prevent disaster. Not only Muslim communities but also non- Muslims who are members of the community participate in carrying out this tradition. As if to be a binding rule, if contrary to tradition it will be isolated or experience inner anxiety. Because according to the beliefs of the perpetrators, tradition has an absolute truth value. Even though there is only one absolute truth that comes from Allah. This means that the nature of a truth should not conflict with one another. Both the truth is in the form of individual traditions, community traditions, traditions of the Messenger of Allah (hadith) or the traditions of Allah himself in setting and regulating the universe (sunnatullah). Including the truth of science, even though it has been through scientific research and testing, still what is called the truth must be able to synergize with various other theories of truth. Through observations in the field it can be concluded that there is a correlation between alms giving and calamity in the implementation of the tradition of "sedekah tolak bala" in the Langkan village community. The truth of the tradition that is believed by the public turned out to also be of true value in the perspective of science and hadith. In science alms referred to as the behavior of doing business with God. The formula is to involve and be helped by God. Furthermore, as a social being related to the truth of sunnatullah, that is, solving problems can be done by helping to solve the problems of others. Such interactions are similar to mutualism symbiosis in patterns of interaction between biotic components in ecosystems. As for the perspective of hadith, there are many ways of narration that mention the virtues of alms making the hadith is authentic and has absolute truth.